Isolation and in vitro screening of Pink Pigmented Facultative Methylobacterium (PPFMs) isolates for the production of phytohormones and ACC deaminase activity from the tea plantations of South India - Marimuthu, S.; Anitha, S.; Ragupathi, G.; Nepolean, P.; Mendez, L.; Thangaraj, P.; Suganthi, S. (Journal of Plantation Crops, 2023)
Pink Pigmented Facultative Methylobacterium (PPFMs) strains were considered as highly eﬃcient growth-promoting bacteria and are ACC deaminase producers which mitigate the drought impact in crop plants. Hence, PPFM strains were isolated from phyllosphere of the tea plantations of south India. A total of 253 bacterial isolates were obtained by using Methanol-AMS medium adopting standard methods. Among the 253 isolates, 105 potential isolates were screened for the production of plant growth hormones viz., IAA, GA3, carotenoids, and 35 potential isolates for ACC deaminase activity. Among 35 isolates tested, 5 isolates viz., MBVPR19D.L23 (51.7 µg/mL), MBANML10H.L06 (45.1 µg/mL), MBVPR19D.L22 (42.0 µg/mL), MBANML10H.L11 (40.5 µg/mL) and MBVPR UPASI L. An H.L13 (40.0 µg/mL) were found to produce higher level of IAA, GA3, and Carotenoids. The highest activity of ACC deaminase was registered in the isolates of Central Travancore namely MBVPR19D.L22 and MBVPR19D.L23 along with one isolate MBKDMVG26H.L37 from Karnataka. The selected strains of MBVPR19 D.L22/23 were identified as Methylobacterium radiotolerans (OL440712) using 16s rRNA molecular technique. This is the first report of isolation of genus Methylobacterium from the acidic environment of tea ecosystem in South India. The present study also suggest that plant growth hormones and ACC deaminase enzyme activity of Methylobacterium species could play a critical role in mitigating the drought stress for a sustainable productivity in tea.